Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.12968/jowc.2017.26.6.314
|View full text |Cite
|
Sign up to set email alerts
|

Management of Fournier's gangrene non-healing wounds by autologous skin micrograft biotechnology: a new technique

Abstract: Fournier's gangrene is an acute bacterial infection producing necrosis of the perineum and external genitalia that generally affects elderly men. Although skin grafts and flaps are the standard procedure for reconstruction, sometimes wounds can become chronic. Rigenera Protocol is a new technique based on autologous skin micrografts that reactivates and supports wound healing. A 40-year-old male with Fournier's gangrene, due to a rectal microperforation following diarrhoea, was treated with surgical debridemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
3
0
4
Order By: Relevance
“…To date, although many clinical studies of the MG technique (Rigenera protocol) have been used to make wound-healing time more effective, research has been limited to case reports [ 14 , 15 , 16 , 17 , 18 , 24 ]. In most reports, the technique has been adopted as an ultimate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To date, although many clinical studies of the MG technique (Rigenera protocol) have been used to make wound-healing time more effective, research has been limited to case reports [ 14 , 15 , 16 , 17 , 18 , 24 ]. In most reports, the technique has been adopted as an ultimate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described the clinical effectiveness of this protocol in the management of chronic wounds, such as dehiscences and ulcers, 69,1214 and the results reported for Case 1 are in line with other authors who have already reported the role of micrografts in the reactivation of wound healing resulting from Fournier’s gangrene. 10…”
Section: Discussionmentioning
confidence: 99%
“…61 Micrografts have also been used for other non-healing wounds, such as those developing following Fournier's gangrene or chronic osteomyelitis, showing a reduction in wounds after approximately 1 month of treatment. 62,63 The efficacy of micrografts has also been reported in repairing cartilage defects, for cartilage regeneration in patients affected by external nasal valve collapse, 64 and the treatment of function-limiting and painful knee chondral injuries. 65 An in vitro study showed that autologous micrografts influenced chondrocyte differentiation, increasing deposition glycosaminoglycans and the presence of collagen II in primary human cells cultured in the presence of micrografts, which supported the formation of chondrogenic micro-masses and acted as a scaffold for chondrocytes.…”
Section: Micrografting: Theory and Applicationsmentioning
confidence: 99%